Verhinderte Meisterwerke - Bartl, Andrea,Kraus, Martin,Erk, Corina (Wilhelm Fink Verlag, 2019)
Unter der Überschrift
9783846763643
Keywords: Film; Scheitern; Literatur; Failure; Literature; Meisterwerk; Movie; masterpiece; film; Fragment